Impact of the Indonesian language course (BIPA) on international student cultural adaptation in Indonesian universities - Ahmed, Touheed; Aman, Aman (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
The Bahasa Indonesia bagi Penutur Asing (BIPA) course plays an essential role in the cultural adaptation at Indonesian universities. However, the precise impact on student cultural integration and academic success has received little attention. This study investigates the impact of BIPA on cultural adaptation of international students, focusing on diverse cultural backgrounds. A mixed methods approach was used, with 123 international students questioned using a Google form survey, and 12 conducting in-depth phone calls to gather the required data. The results show that BIPA significantly improves language proficiency and cultural understanding. Language barriers emerge as the primary challenges to adaptation, emphasising the importance of language acquisition. Tailored support mechanisms within Indonesian universities are deemed essential to meet the diverse needs of international students. The recommendations include optimising BIPA programs and creating supportive environments for students.